Development of Islamic Education Curriculum Model Curriculum 2013 (K13) - Dwi Noviatul Zahra (Al-Hayat: Journal of Islamic Education, 2019)
The development of an Islamic religious education curriculum (PAI) is an activity to produce a PAI curriculum and a process that links one component to another to create a better Islamic education curriculum (PAI). The curriculum component must consist of at least four parts, namely objectives, contents, processes, and assessments. This study discusses in depth the development of the curriculum in the Indonesian curriculum for the 2013 Curriculum model. This study aims to determine the extent to which the curriculum development curriculum for the 2013 curriculum model PAI. This study uses a literature review method. Data collection is done through documentation study techniques. The results of this study indicate that the curriculum development of the 2013 curriculum in the PAI is very significant, oriented towards realizing character education, creating education with local insight and creating a cheerful and friendly culture. Pengembangan kurikulum Pendidikan Agama Islam (PAI) adalah kegiatan menghasilkan kurikulum PAI, dan proses yang mengkaitkan satu komponen dengan komponen yang lainya untuk menghasilkan kurikulum pendidikan agama Islam (PAI) yang lebih baik. Komponen kurikulum setidaknya harus terdiri dari empat komponen yaitu tujuan, isi, proses dan penilaian. Penelitian ini membahas secara mendalam mengenai pengembangan kurikulum PAI model Kurikulum 2013. Penelitian ini bertujuan untuk mengetahui sejauh mana pengembangan kurikulum PAI model Kurikulum 2013. Penelitian ini menggunakan metode kajian pustaka.Pengumpulan data dilakukan dengan teknik studi dokumentasi. Hasil penelitian ini menunjukkan pengembangan kurikulum PAI Kurikulum 2013 pada ranah ini sangat signifikan, yang berorientasi pada mewujudkan pendidikan berkarakter, menciptakan pendidikan berwawasan lokal serta menciptakan pendidikan yang ceria dan bersahabat.